Infinite possibilities of social dreaming - Lawrence, W. Gordon (Karnac, 2007)
The chapters in this book on Social Dreaming highlight the limitless potential of free association and amplification within the practice of social dreaming.
Includes bibliographical references and index.
Keywords: Psychoanalysis; Social dreaming; Psychology